Interpretation of rurality and the situation of land use in Hungary - Harsányi, Endre; Fejér, Péter; Kutasiné Nagy, Irén; Rátonyi, Tamás (Acta Agraria Debreceniensis, 2014)
The summarizing data collection of our study has been carried out in the scope of the FP7-REGPOT-2010-1 ’UD_AGR_REPO’ project as a part of the cooperation with the University of Lincoln. The University of Lincoln is an important partner of the project, the knowledge transfer activities that have been carried jointly with them are multilateral. One of the most important cooperation areas is the analysis of rural areas, rurality itself, determination of breakout points, exploration of alternative income sources, diversification possibilities. Some part of the work of the University of Lincoln on the field of rural development is based on the assessment and documentation global similarities and differences of rural areas. Present study also contributes to that work, it has been prepared on the request of the University of Lincoln with the aim of providing insight into the special political and economic changes/processes that took place in Hungary, and through them into the structure and operation of the unique Hungarian rural areas. The study first positions the definition of rurality and rural areas into context on the basis of official EU and Hungarian legal classification. Then it covers the important agricultural nature of Hungary, which significantly determines the possibilities and properties of Hungarian rural areas. The further description of rural areas is completed by some historical summary, the introduction of ownership changes, detailed description of employment and income conditions and finally by the listing of breakout points of rural areas as a conclusion.